Use of tobacco and alcohol by Swiss primary care physicians: a cross-sectional survey - Künzi Beat; Goehring Catherine; Bouvier Gallacchi Martine; Sebo Paul; Bovier Patrick A (BMC, 2007)
Abstract Background Health behaviours among doctors has been suggested to be an important marker of how harmful lifestyle behaviours are perceived. In several countries, decrease in smoking among physicians was spectacular, indicating that the hazard was well known. Historical data have shown that because of their higher socio-economical status physicians take up smoking earlier. When the dangers of smoking become better known, physicians began to give up smoking at a higher rate than the general population. For alcohol consumption, the situation is quite different: prevalence is still very high among physicians and the dangers are not so well perceived. To study the situation in Switzerland, data of a national survey were analysed to determine the prevalence of smoking and alcohol drinking among primary care physicians. Methods 2'756 randomly selected practitioners were surveyed to assess subjective mental and physical health and their determinants, including smoking and drinking behaviours. Physicians were categorised as never smokers, current smokers and former smokers, as well as non drinkers, drinkers (AUDIT-C < 4 for women and < 5 for men) and at risk drinkers (higher scores). Results 1'784 physicians (65%) responded (men 84%, mean age 51 years). Twelve percent were current smokers and 22% former smokers. Sixty six percent were drinkers and 30% at risk drinkers. Only 4% were never smokers and non drinkers. Forty eight percent of current smokers were also at risk drinkers and 16% of at risk drinkers were also current smokers. Smoking and at risk drinking were more frequent among men, middle aged physicians and physicians living alone. When compared to a random sample of the Swiss population, primary care physicians were two to three times less likely to be active smokers (12% vs. 30%), but were more likely to be drinkers (96% vs. 78%), and twice more likely to be at risk drinkers (30% vs. 15%). Conclusion The prevalence of current smokers among Swiss primary care physicians was much lower than in the general population in Switzerland, reflecting that the hazards of smoking are well known to doctors. However, the opposite was found for alcohol use, underlining the importance of making efforts in this area to increase awareness among physicians of the dangers of alcohol consumption.